THE ROLE OF CORPUS OF CONTEMPORARY AMERICAN ENGLISH (COCA) IN ENHANCING WRITING INSTRUCTION - Radjabova, Gulnoza (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2024)
The most challenging language skill for most EFL students is considered to be writing skill because of limitation of their vocabulary repertoire and their uncertainty regarding the use of more advanced vocabulary. This article explores experimental research on the applications of COCA in teaching writing, focusing on its role in enhancing vocabulary acquisition, improving grammatical accuracy, promoting genre-specific writing skills, and fostering overall writing proficiency.